The effect of firewood combustion cookstove types on indoor air pollution and deforestation in selected rural houses of Ethiopia - Fekadu, Miftah; Molla, Moges; Hailu, Birhanu (Frontiers in Environmental Science, 2024)
Indoor air pollution occurs in a microenvironment such as residential home, closed working places or industries in which people spend a large part of their time. Cooking or baking food in traditional or open three stone cookstoves by using firewood is the cause of kitchen-related smoke indoor air pollution and deforestation. Then modifying traditional firewood cookstove could reduce emission of indoor air pollutants. The objective of the present study was to determine the effect of firewood cookstoves types on indoor air pollutant, emission reduction and deforestation in Bure, Ameya, and Dalocha woredas (districts) of Ethiopia. Indoor air pollutants such as carbon monoxide (CO), carbon dioxide (CO 2 ), sulfur dioxide (SO 2 ), particulate matters were measured in three replicates for 3 minutes within 1-hour average cooking time by automatic gas sensor. The cooking place mostly was the same room as the sleeping place without separate kitchen. The installation of improved cookstoves was without chimney (smoke outlet) and with wider spaces left for firewood inlet. In improved injera baking cookstoves, the mean emission of CO was 1004.80 mg/m 3 , 33.00mg/m 3 and 53.85mg/m 3 in Bure, Ameya and Dalocha woreda, respectively, which were lower than the emission from open cookstoves. The mean concentration of PM2.5µm in open cookstoves in Bure, Ameya and Dalocha woreda was 124.50mg/m 3 , 0.53 mg/m 3 and 0.04 mg/m 3 , respectively, which are higher than the emission from improved stoves. In Bure woreda households CO exposure was above 26 times the permissible limit of WHO standards. Biomass consumption was positively correlated with moisture content of wood (P<0.05). Improved cookstoves reduced indoor air pollutants by 13-81%, and carbon emission and deforestation by 20-41% when compared with the open three stone cookstoves. Indoor air pollutants are risks to health and climate change problems. Therefore, there should be awareness creation on the health effects of firewood smoke indoor air pollution, ventilation of cooking places and installation of chimney.